SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP DENGAN METODE AHP (STUDI KASUS PADA CV MAJU BERSAMA) - Godzallez, Noel Nicolaz; Sulistiowati, Sulistiowati; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
CV Maju Bersama is a company engaged in the sale of gadgets and laptops. CV Maju Bersama sells various types of laptops ranging from those used for offices to laptops used for specifically playing games. Currently CV Maju Bersama has 9 stores and their surroundings spread around Madiun and has a total of 150 employees in all stores. With the current business process, it is found that the problem is that customers often find it difficult to choose the laptop they need due to various offers of laptops from employees, this causes customers to buy laptops that do not suit their needs. This causes impacts such as the purchased laptop cannot be used according to customer needs. On the other hand, based on the results of interviews with five (5) store employees, it was found that so far employees also sometimes have difficulty choosing laptops when there are many visitors. This results in a queue of customers who will buy a laptop. Based on the problems above, we need an application with a web-based Analytical Hierarchy Process (AHP) method to help customers choose a laptop to suit their needs. Meanwhile, store employees assist customers in determining laptops to suit customer needs.